2003
DOI: 10.1016/j.exppara.2003.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Dominant antibody responses to Fucα1-3GalNAc and Fucα1-2Fucα1-3GlcNAc containing carbohydrate epitopes in Pan troglodytes vaccinated and infected with Schistosoma mansoni

Abstract: The development of the humoral anti-glycan immune response of chimpanzees, either or not vaccinated with radiation-attenuated Schistosoma mansoni cercariae, was followed during 1 year after infection with S. mansoni. During the acute phase of infection both the vaccinated and the control chimpanzees produce high levels of immunoglobulin G (IgG) antibodies against carbohydrate structures that are characteristic for schistosomes carrying the Fucalpha1-3GalNAc and Fucalpha1-2Fucalpha1-3GlcNAc motifs, but not to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 39 publications
2
32
1
Order By: Relevance
“…For S. mansoni, it has been shown previously that multifucosylated GSL glycans remained expressed in later stages of schistosomula development (9) and are surface exposed (28), and they have been shown to be major targets of antibody response in sera of infected individuals (47)(48)(49)51). The reason we did not observe significant binding for lung LN ASC probes might be the differences in the expression of these glycans between S. mansoni and S. japonicum.…”
Section: Discussioncontrasting
confidence: 50%
“…For S. mansoni, it has been shown previously that multifucosylated GSL glycans remained expressed in later stages of schistosomula development (9) and are surface exposed (28), and they have been shown to be major targets of antibody response in sera of infected individuals (47)(48)(49)51). The reason we did not observe significant binding for lung LN ASC probes might be the differences in the expression of these glycans between S. mansoni and S. japonicum.…”
Section: Discussioncontrasting
confidence: 50%
“…For testing the specificity of exoglycosidases used in this study, the synthetic glycoconjugates Fuc␣1-3GalNAc␤1-4GlcNAc␤1-3Gal␣1-(CH 2 ) 5 -squarate (F-LDN-tag) and GalNAc␤1-4(Fuc␣1-3)GlcNAc␤1-3Gal␣1-(CH 2 ) 5 -squarate (LDN-F-tag), recovered following derivatization with diethylsquarate during a protein coupling procedure (25,26) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Later studies revealed that antibody levels to LDN-dF and FLDN epitopes were strikingly higher than those against LDN, LDNF, and monomeric Le x in vaccinated or infected chimps and infected human cohorts. Interestingly, the anti-LDN-dF and anti-FLDN antibodies were predominantly IgGs, whereas anti-Le x , anti-LDN, and anti-LDNF were IgMs; however, this was not always consistent in human studies (25,26,41,70). Note that in mice, the acute infection is marked by IgM antibodies to LDNF, LDN, and Le x (24).…”
Section: Discussionmentioning
confidence: 77%
“…The lectin HPA (Helix pomatia agglutinin) was purchased from Sigma-Aldrich. An anti-LDN (IgG, clone Y1H5), an anti-LDNF (IgG, clone L6B8), an anti-Le x (IgM, clone 5F1), two anti-LDN-dF (IgM, clone 290-2D9-A; IgM, clone 290-4A8), and an anti-Man 3 GlcNAc 2 (M3GN2; IgM, clone 100-4G11-A) MAb, as well as an anti-FLNDF antibody (IgG, clone F2D2), were developed as MAbs by the production of hybridomas from spleens of mice that had been infected with S. mansoni by using methods described previously (16,(39)(40)(41)(42). The anti-horseradish peroxidase (HRP) antibody (anti-peroxidase, polyclonal rabbit IgG; P7899) was purchased from Sigma-Aldrich and used to detect core ␣3 fucose and core xylose (CF/CX) determinants (43,44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation